The relation between social support and posttraumatic growth in women treated for cancer - Mazurkiewicz, Agnieszka; Makara-Studzińska, Marta (Medycyna Paliatywna/Palliative Medicine, 2015)
Aim of the study : The purpose is to analyze the connection between posttraumatic growth and social support, and its three aspects: emotional support, practical support, and social integration. It is also the aim of the current study to identify and compare the results of social support scale and its three aspects among women with low, average and high level of posttraumatic development. Material and methods: Forty women treated with radiotherapy for cancer have been examined. 30 of them were inpatients in the II Division of Radiotherapy of Oncology Center in Lublin, 10 of them were outpatients. Patients completed the Posttraumatic Growth Inventory (PTGI) and Social Support Scale (SOZ-U K-22). Results : There is a significant, statistically positive correlation (r = 0,471) between posttraumatic growth and social support. A positive correlation appears also between posttraumatic growth and two out of three aspects of social support (emotional support [r = 0,372] and social integration [r = 0,614]). Women with the average level of posttraumatic growth achieved the highest average in social support. Conclusions : Social support is an important factor determining the influence of posttraumatic growth among women treated with radiotherapy for cancer. There is a significant, statistically positive correlation between posttraumatic growth and social support, and its two aspects: emotional support and social integration. The most important feature of social support for women treated with radiotherapy for cancer is its adequacy in terms of patient’s needs.